2014
DOI: 10.1007/s12264-014-1463-y
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging in ischemic cerebrovascular disease: current status and future directions

Abstract: Cerebrovascular diseases are caused by interruption or significant impairment of the blood supply to the brain, which leads to a cascade of metabolic and molecular alterations resulting in functional disturbance and morphological damage. These pathophysiological changes can be assessed by positron emission tomography (PET), which permits the regional measurement of physiological parameters and imaging of the distribution of molecular markers. PET has broadened our understanding of the fl ow and metabolic thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 115 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…Previous studies have found imaging of the oxygen extraction fraction (OEF) in acute stroke imaging to be useful for distinguishing and determining the extent of the tissue at risk of infarction and the ischemic core [19]. In both tissue areas, impaired perfusion causes not only reduced supply of oxygenated hemoglobin but also slowed removal of deoxyhemoglobin [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found imaging of the oxygen extraction fraction (OEF) in acute stroke imaging to be useful for distinguishing and determining the extent of the tissue at risk of infarction and the ischemic core [19]. In both tissue areas, impaired perfusion causes not only reduced supply of oxygenated hemoglobin but also slowed removal of deoxyhemoglobin [7].…”
Section: Discussionmentioning
confidence: 99%
“…In both tissue areas, impaired perfusion causes not only reduced supply of oxygenated hemoglobin but also slowed removal of deoxyhemoglobin [7]. Therefore, since OEF is increased within tissue at risk of infarction as demonstrated with PET [19], the accumulation of deoxyhemoglobin is expected to increase accordingly, as detected in previous studies [7,12]. Bauer et al showed significant differences in T2′ values between perfusion-impaired, diffusion-restricted, and healthy tissue in a smaller sample size; yet, T2′-measurements demonstrated the highest values within the infarct core, which is not expected to contain tissue with the highest oxygen extraction fraction in acute stroke, as proven by PET previously [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically stroke is evaluated primarily through anatomic and functional magnetic resonance imaging, with molecular approaches limited due to a lack of viable radiotracers for this indication beyond those used to measure perfusion with single photon emission computed tomography (15). A PET agent for sEH may enable distinction between AD and VCI in vivo, rather than having to rely on postmortem observation of Aβ plaques and neurofibrillary tangles (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…PET is regarded as the “gold standard” that affords an advantage of quantitatively assessing multiple parameters related to the cerebral physiological and metabolic conditions. Evaluation of CCCI can be accomplished with PET, which estimates cerebral perfusion via measuring the CBF and oxygen extraction fraction (OEF) . However, it is not considered as a first‐line option because of a relatively high cost and demand for technique as well as a low penetration rate.…”
Section: Imaging Featuresmentioning
confidence: 99%